Trace Metals Distribution in Tissues of 10 Different Shark Species from the Eastern Mediterranean Sea - Eleni Roubie; Sotirios Karavoltsos; Aikaterini Sakellari; Nikolaos Katsikatsos; Manos Dassenakis; Persefoni Megalofonou (Fishes, 2024)
As long-living apex predators, sharks tend to bioaccumulate trace metals through their diet. The distribution of Al, As, Cd, Co, Cr, Cs, Cu, Fe, Mn, Ni, Pb, V, Zn and Hg in different tissues (muscle, liver, heart, gills and gonads) of large-size (58–390 cm) sharks, some of which rare, of the eastern Mediterranean Sea was studied. Trace metals analyses in samples originating from ten different Chondrichthyes species were performed by inductively coupled plasma–mass spectrometry (ICP-MS) and Cold Vapor Atomic Absorption Spectrometry (CVAAS) for Hg. Data on trace metal levels are for the first time reported herewith for the species O. ferox and H. nakamurai. Higher median concentrations of trace metals were generally determined in the liver. The concentrations of Hg, Cs and As in the muscle increased proportionally with body length. Statistically significant differences between sexes were recorded for Hg, Cr, Ni and As (p = 0.015) in the muscle tissues of P. glauca. Muscle tissue Hg concentrations exceeded the EU maximum limit (1 μg g−1 wet weight) in 67% of the individuals sampled, with the highest concentrations detected in O. ferox and S. zygaena, whereas regarding Pb (limit 0.30 μg g−1 ww), the corresponding percentage was 15%. Arsenic concentrations were also of concern in almost all shark tissues examined.